Respuesta :

Answer:

(-1/3, 3/4)

Step-by-step explanation:

9x + 8y = 3

6x - 12y = -11

Let's solve the system by eliminating x. We need the coefficients of x to be additive inverses, so they will add to zero eliminating x. The LCM of 9 and 6 is 18. Let's multiply both sides of the first by 2 and both sides of the second equation by -3.

18x + 16y = 6

-18x + 36y = 33

The coefficients of x are 18 and -18, which add to zero. Now we add these two equations.

52y = 39

y = 39/52

y = 3/4

Now we substitute y with 3/4 in the first equation and solve for x.

9x + 8y = 3

9x + 8(3/4) = 3

9x + 6 = 3

9x = -3

x = -3/9

x = -1/3

Solution: (-1/3, 3/4)